Violencia sexual en niños y adolescentes varones en el mundo: una revisión integrativa (2020)
Objective: Collect, summarize, and analyze current scientific publications on Child Sexual Violence (CSV) in male children and adolescents worldwide between 2014 and 2019. Method: An integrative review was conducted using a systematic search of studies pu